Two rivals, one bed - Day, Zuri (Day, Zuri. Eddington heirs, 2022)
Irresistible desire between rivals puts everything at risk. Maeve Eddington must defend her family's billion-dollar conglomerate in a lawsuit. But her opposing counsel is playboy Victor Cortez, who leaves her weak with desire. Maeve is determined to resist her cocky opponent to avoid compromising her case. She knows the risks of getting involved with a man like him Victor very much wants to get to know her better If only there wasn't a lawsuit in the way.